Early Risk Assessment In Right Ventricular Infarction By TIMI Risk Score - Haque, MA; Khan, MR; Momen, A; Rahman, Z; Chowdhury, AW; Shahabuddin, M; Faruque, GM (Cardiovascular Journal, 2012)
Background: Inferior myocardial infarction complicated by right ventricular infarction is associated with a greater risk of in-hospital mortality and cardiovascular related complications. Early risk stratification of patients with right ventricular infarction is crucial for appropriate management and reduction of adverse cardiac events. The development of TIMI risk score has provided a useful tool to quickly and easily stratify patients with right ventricular infarction. We conducted this study to evaluate the prognostic value of TIMI Risk Score analysis in patients with right ventricular infarction. Methods: This observational study was conducted in the department of Cardiology in NICVD, Dhaka, from July 2006 to June 2008. Considering inclusion and exclusion criteria, a total of 60 patients with right ventricular infarction were evaluated. All the patients were evaluated clinically and ECG was done after admission. Patients were categorized into two groups by TIMI risk scoring. Patients with low TIMI risk score(0-3) were in Group-I and patients with high TIMI risk score(4- 14) were in Group-II. Results: The study revealed no statistically significant difference among the patients of two groups (p>0.05) in relation to sex, weight, risk factors and presenting complaints. Analysis revealed statistically significant difference among the patients of two groups (p<0.05) in relation to age, duration of chest pain, clinical parameters, Killip class of heart failure and LVEF. Regarding inhospital outcome, 51.7% patients developed complications during the study period and all the complications were more in group II patients with high TIMI risk score (4-14). Death (18.3%) was the most common complication followed by cardiogenic shock (15.0%), complete heart block (6.6%),cardiac arrest (6.6%),VT(3.3%)and 2nd degree heart block (1.6%). Conclusion: This study indicates that on admission - TIMI risk score analysis can identify patients with right ventricular infarction at higher risk for in-hospital mortality and morbidity DOI: http://dx.doi.org/10.3329/cardio.v5i1.12273 Cardiovasc. j. 2012; 5(1): 51-56